PASANG SURUT HUBUNGAN ANTARA MAHKAMAH AGUNG DENGAN KOMISI YUDISIAL DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Muhammad Fauzan (Jurnal Dinamika Hukum, 2012)
The relationship between the Supreme Court by the Judicial Commission in the Republic of Indonesia system is not harmonious, this is due to the first, the disharmony between the law on judicial power, including the law on Judicial Power, the law on the Supreme Court, the law on Constitutional Court and the law on the Judicial Commission. Both of the leadership character that exist in the Supreme Court and the Judicial Commission were too emphasizes in ego that one sector feel more superior than the others. To create a harmonious relationship between Supreme Court and Judicial Commission can be done by establishing intensive communication between both of them and by improvement in legislation. Keywords : relation, Supreme Court, Judicial Commission